How to train your dragon. Homecoming [videorecording (DVD)] - Cowell, Cressida (Universal Pictures Home Entertainment, 2019)
When it becomes clear that the new generation of Vikings doesn't remember the bond between dragon and human. Hiccup sets a plan to celebrate dragons with a grand Snoggletog holiday pageant and gets a heartwarming surprise visit from Toothless for one more adventure.